2020
DOI: 10.1016/j.scitotenv.2020.139574
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of polycyclic aromatic compounds (PACs) to the Sydney rock oyster (Saccostrea glomerata) from sediment matrices of an economically important Australian estuary

Abstract: Improving risk assessment and remediation rests on better understanding of contaminant bioavailability. Despite their strong toxicological attributes, little is known about the partitioning behaviour and bioavailability of polar polycyclic aromatic hydrocarbons (PAHs) in aquatic environments. The present study provides an insight into the bioavailable fractions of polar PAHs and their parent analogues in the tissues of the Sydney rock oyster, Saccostrea glomerata, a model aquatic bio-indicator organism. The co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…The PIOM ( n = 9) and background water samples ( n = 3) were extracted following the US EPA 3051A method and analyzed via inductively coupled plasma–mass spectroscopy (ICP–MS) (Supporting Information S3). Details of the PAH and PFAS quantification in the PIOM ( n = 9 for each segment) and background water ( n = 3) are provided in Supporting Information S4 and S5, respectively. Further details on the analytical methods and quality control procedures can be found in the Supporting Information and previous publications by the research team. , …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The PIOM ( n = 9) and background water samples ( n = 3) were extracted following the US EPA 3051A method and analyzed via inductively coupled plasma–mass spectroscopy (ICP–MS) (Supporting Information S3). Details of the PAH and PFAS quantification in the PIOM ( n = 9 for each segment) and background water ( n = 3) are provided in Supporting Information S4 and S5, respectively. Further details on the analytical methods and quality control procedures can be found in the Supporting Information and previous publications by the research team. , …”
Section: Methodsmentioning
confidence: 99%
“…The Port Stephens estuary has a known issue of PFAS contamination and legacy tar deposits containing PAHs in sediments underlying oyster leases, potentially contributing to elevated levels of these contaminants in the PIOM. The concentration of PAHs in the sediments (mean, 6442.94 μg g –1 ) at 33 sites from the surrounding area has previously been investigated by our research group . The elevated levels of metal­(loid)­s, PAHs, and PFAS in the PIOM may also be due to the hydrophobic/hydrophilic organic distributions in the extracellular polymeric substances, and the presence of polysaccharides, proteins, lipid membranes and charged groups ( e.g.…”
Section: Environmental Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…36 Qiao et al 25 investigated the distribution of 16 PPAHs, 4 MPAHs, 6 OPAHs, and 8 XPAHs in 3 rivers in northern China, showing that the concentration of OPAHs (321 ± 651 ng/L) was higher than those of PPAHs (158 ± 105 ng/L), APAHs (28 ± 22 ng/L), and XPAHs (30 ± 12 ng/L). Idowu et al 26 investigated the distribution of 14 parent PAHs, 7 OPAHs, 3 NPAHs, and 9 HPAHs in Australia and found that the concentrations of PPAHs (50−9640 ng/L) were higher than those of NPAHs (30−6660 ng/L), OPAHs (110−2180 ng/L), and HPAHs (40−120 ng/L). The NPAH concentrations in the present study were higher than those reported in the Meichuan River (n.d.−5.2 ng/L) and Luchuan River (n.d.− 19.7 ng/L) 23 but lower than those in Japan (604 ng/L).…”
Section: Occurrence Of Pacs In Surfacementioning
confidence: 99%
“…Among the hundreds of PAHs, United States Environmental Protection Agency (US EPA) has promulgated sixteen PAHs as significant contaminants, due to their mutagenic and toxic effects. These have been extensively studied in numerous environments such as soil, dust, natural waters and living organisms (e.g., Sarigiannis et al 2015;Sun et al 2016;Zheng et al 2016;Idowu et al 2020;Nováková et al 2020;Peng et al 2020).…”
Section: Introductionmentioning
confidence: 99%